Cost and Financing of Education and its Impact on Coverage and Quality of Services and Efficiency and Equity in Sub-Saharan African Countries - (:unkn) unknown (My University, 2007)
In this chapter, we take mostly an international comparative perspective limited to Sub-Saharan African countries. First, we analyse first the macro picture and the public finance dimension, analyzing the systemic choices made in the distribution of public resources across levels and types of education. Second, we move to unit cost estimates and the factors accounting for their level in a given country and to their variation across the different countries of the region. Finally, we examine the implication of the choices made in the financial dimension upon outcomes (coverage and quality of educationl services), birnging issues of efficiency and equity into the analysis.
Keywords: African Research